Frequência e intensidade de infecção por helmintos gastrintestinais de caprinos leiteiros criados em condições semi-extensivas no município de Afonso Bezerra - RN - Bezerra, Adiza Cristiane Avelino (Universidade Federal Rural do Semi-Árido, 2010)
The goat rearing constitutes a great social and economic importance activity to the Brazilian Northeast. However, sanitary problems represent a relevant limitation for the goat production, especially gastrointestinal parasitism due to high mortality rates and, principally, leading to low productivity of livestock due to subclinical parasitosis. aiming to seek grant for the control of nematode parasites in small ruminant in Rio Grande do Norte state, an epidemiological investigation of gastrointestinal helminths that affect dairy goats in Afonso Bezerra city, RN was done. The study was conducted in a private property from April 2008 to March 2009. Three free of gastrointestinal nematodes goats (tracers) were necropsied once a month to recover the gastrointestinal contents. This material was taken to the Animal Parasitology Laboratory UFERSA to be recovered, counted and identificated the gastrointestinal nematodes. The results showed that the most common helminths found were Haemonchus contortus in the abomasum (57.23%), Trichostrongylus columbriformis in the small intestine (40.54%) and Oesophagostomum columbianum in the large intestine (1.42%). Soon after the rainy season, the parasitic infection was more elevated with gradual decrease in the dry season, following the curve of precipitation.
Frequency and intensity of gastrointestinal helminthes in dairy goats under semi-extensive management in Afonso Bezerra city, Rio Grande do Norte state, Brazil
Keywords: Goats; Helminths; Frequency; Epidemiology; Caprinos; Helmintos; Frequência; Epidemiologia; CIENCIAS AGRARIAS::MEDICINA VETERINARIA